Socio-Demographic and Blood Group Findings in Children with Acute Leukemia: a single cancer center experience - Abdulkareem, Awayi Ghazy; Ali, Nawroz Othman; Mahmood, Chnar Ali; Omer, Warzer Dlshad; Ahmad, Hiwa Mustafa; Ali, Ari Karim (Sulaimani Journal for Pure and Applied Sciences, 2020)
Leukemia is a cancer of white blood cells, in which the bone marrow produces irregular white blood cells. These cells swarm out the solid blood cells. In intense leukemia, the cells are highly irregular, and their number increments quickly. Acute lymphocytic leukemia (ALL) most common childhood malignancy in most parts of the world. The etiology of childhood leukemia is unknown and is probably multifactorial. Leukemia can often be cured. However, the association between this type of cancer and ABO blood group is not established. The present study aimed to identify the association between blood groups and Rh types with childhood leukemia. For this purpose, a quantitative design retrospective study was conducted between the 1st December 2019 and the 30th January 2020 on the records of 100 patients who were under 18 years old with diagnosed leukemia, treated, and followed at the pediatric unit of Hiwa Hospital in Sulaimaniyah. Data on patients’age, gender, residence, age at diagnosis, and blood group were collected. According to the retrospective analysis, 100 patients who met the diagnosis of ALL and acute myeloid leukemia (AML) were 18 years or younger, most of them had ALL (81%), 85% lived in urban areas, 63% were male, and A+ was the most common blood group (36%). Also, there was no statistically significant association between ABO blood group and diverse autonomous factors with childhood leukemia. ABO blood groups can be used as an effective technique to understand the etiology of hematological malignancies, particularly if they are assessed within the ground of later atomic writing of such hereditary polymorphism.
Keywords: Socio-demographic; ABO blood group; children; Leukemia; cancer